Factors Influencing Customer Satisfaction? A Case Study of Watson’s Personal Care Store in Malaysia - Utama, Anak Agung Gde Satia; Balqis, Alia; Damia, Amalia; Aiman, Amir; Suvarie, Andrea; Hilmin, Siti Nur (AIBPM Publisher, 2023)
Watson’s Personal Care Store is Asia's top health and beauty retailer since 1828 which strives to satisfy customers' expectations through marketing strategies, a wide selection of high- quality products at excellent value and an interesting customer experience. Approximately three billion customers shop both in stores and online every year. To remain competitive in the retail business, Watsons is constantly seeking efficient ways to satisfy customers' needs while also overcoming the growing competition's challenges. This study's objective is to determine whether service quality, perceived trust, perceived convenience, and product pricing have a significant correlation with customer satisfaction, which may lead to customer loyalty. This research will examine approximately 150 Watson’s customers from Malaysia. The respondents were asked to answer a questionnaire via Google Form that researchers have spread through online platforms. SPSS was used to analyze our data. Once the data has been collected the results from the respondents were expected that service quality does affect customer loyalty and satisfaction. Our results indicate that service quality, perceived trust, perceived convenience, and product pricing have a significant relationship with customer satisfaction. Additionally, we discovered that customer satisfaction has an approximately complete mediating effect on customer loyalty. The findings will reveal new perspectives on customer satisfaction of Watson’s Personal Care Store.